Islamic Education in Non Formal Institutions: The Role of Majelis Taklim Based on Indonesian Local Wisdom - Asrin, Ahmad (Fitrah: Journal of Islamic Education, 2024)
Indonesia is known for its rich local wisdom, including in Islamic education practices. However, the tide of modernization has eroded some of these values. In fact, local wisdom has unique characteristics that can be preserved to strengthen the Islamic values of students. This study analyzes the role of the Majelis Taklim Keluarga Sakinah as a non-formal educational institution in improving the quality of family life, particularly in spiritual, social, and economic aspects. This study uses a qualitative research method based on case studies, with a focus on the various Islamic education programs implemented by the Sakinah Family Majelis Taklim. The results reveal that participation in Majelis Taklim activities has a positive impact on understanding Islamic values, strengthening family harmony, and increasing social awareness. Additionally, it contributes to improving economic well-being and providing social security for its members. The implications of this study indicate that the Majelis Taklim serves as a non-formal educational institution and a social transformation agent in building harmonious families. These findings support Jack Mezirow's theory of transformative learning, which emphasizes the importance of critical reflection in changing individual perspectives. Support from various stakeholders is needed to strengthen the role of the Majelis Taklim in improving the quality of life for Muslim families.